FINANCIAL INSTRUMENT FOR PROVIDING CLIMATIC SECURITY: PROBLEMS OF USE IN THE WORLD AND IN UKRAINE (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The article analyzes the problems of the use of financial instruments that affect the observance of climate security. The article also explores the peculiarities of the use of financial climatic tools in the leading countries of the world and the problems of using some of them in Ukraine, as the financial resources of our country are extremely limited. The expediency of introducing changes in the use of such financial climate instruments as green tariff, carbon tax, environmental taxes on fuel, as well as the shortcomings of the power methods of the introduction of the latter, were substantiated.It was shown that the mass protests of the so-called «yellow vests» in France in November-December 2018 against the introduction of the environmental tax on fuel proved that under current conditions, public financial climate restrictions should take into account the financial ability of their compliance with households, businesses (especially small and medium), local authorities. Therefore, individual states and international organizations need to better predict not only the positive effects of the introduction of financial climate instruments, but also the negative effects on incomes of the general population.The current stage of globalization and its negative impact on the climate necessitates the cooperation of national governments in addressing climate security issues, which necessitates the creation of inter-state financial institutions for the joint resolution of global climatic problems. One of them could be the creation of the International Climate Fund, as well as the introduction of a world wealth tax.In the framework of the mechanism of providing climate security in Ukraine in today's conditions, it is first of all to include such financial instruments as environmental taxes, incentives (first of all, green tariffs) and fines, as well as investments and loans aimed at improving the climatic conditions of reproduction of factors of production.
Keywords: climate security, financial instruments, carbon tax, green tariff, EU, Ukraine.